Fiscal shocks, public debt, and long-term interest rate dynamics - Luigi Marattin; Paolo Paesani; Simone Salotti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
Public finances worldwide have been severely hit by the 2008-2009 Great Recession, stimulating the debate on the consequences of growing fiscal imbalances. Building on Paesani et al. (2006), this paper focuses on the USA, Germany and Italy over the 1983-2009 period and studies the effects of fiscal shocks and government debt accumulation on long-term interest rates, both nationally and across borders. Based on a theoretical framework, the empirical analysis disentangles permanent and transitory components of interest rates dynamics finding that sustained debt accumulation leads, at least temporarily, to higher long-term interest rates. This is particularly true for the Italian case. There is also evidence of significant cross-country linkages, mainly between Italy and the USA.
Keywords: E6; H63; 330